Studi Peristiwa Pandemi Covid-19 Terhadap Harga Saham Di Sektor Pariwisata - Azmiyanti, Rizdina; Suhartini, Dwi (APSSAI ACCOUNTING REVIEW, 2022)
This study aims to study the events of the COVID-19 pandemic on the share price of the tourism sector in Indonesia. This research is quantitative research with an event study approach. The documentation method is used to retrieve data of stock prices. This study uses purposive sampling to determine the number of samples, which are 28 tourism sector companies listed on the Indonesia Stock Exchange. Through this study, an observation was made on the stock price of the tourism sector to analyze the abnormal returns that occurred from the announcement of the first Covid-19 case in Indonesia. The results show that at the beginning of the Covid-19 pandemic in Indonesia, there were abnormal returns in the tourism industry shares, before the announcement of the first case the market had already reacted to the tourism industry shares because government support was being intensively implemented to advance the tourism sector. However, after the COVID-19 pandemic officially entered Indonesia, the share price of the tourism industry tended to react negatively due to the implementation of social restrictions in social activities. The results of this study contribute to one of the benchmarks for the Indonesian government to formulate economic recovery policies in the tourism sector.